olume 7. Num 2. Abstract Book. V International Congress of AEPROMO. VI International Congress of IMEOF (Ozone Therapy Global Journal, 2017)
Supplement. Abstract Book AuthorsAdriana Schwartz AbstractAbstract Book.V International Congress of AEPROMOVI International Congress of IMEOF